Zjawisko cyberprzestępczości a polityka cyberbezpieczeństwa w regulacjach prawnych Rady Europy, Unii Europejskiej i Polski - Karatysz, Mateusz (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
In the last decade there has been a sudden and rapid development of the Internet. Together with its improvement, the issue of network security has become an important topic of a discussion over the international security mechanisms. The Internet, nowadays considered as space unrestricted by time or distance, has become an ideal place for new, previously unknown offenses and misdemeanours. Ipso facto, network is now an area that requires measures to ensure safety of its users. Although a cybercrime is currently a subject of the work on complementary legal solutions on both national and international levels, we can wonder if thanks to them the Internet will become a safe place one day.